Patterns of Daily and Non-Daily Nicotine Pouch Use Among U.S. Adults: An Exploratory Analysis of Use Contexts, Harm Perceptions, and Health Characteristics, 2025 - Delvon T. Mattingly; Meman Diaby; Saber Feizy; William A. Middleton; Josie Ricketts; Joy L. Hart; Melinda Ickes; Bethany Shorey Fennell (International Journal of Environmental Research and Public Health, 2026)
This study examined differences between daily and non-daily nicotine pouch (NP) use by adults across various contexts in the United States (U.S.). Data were drawn from a cross-sectional survey of adults (≥18 years) reporting past-year NP use (N = 1009). Differences between daily and non-daily use groups were assessed using chi-square tests. Among the sample, 17.5% reported daily NP use. Daily use was associated with greater intensity, higher nicotine strength, and distinct situational use, including at home, while commuting, and at work or school (all p < 0.01). Adults who used daily more often endorsed motivations related to stress reduction, craving management, convenience, and product appeal (p ≤ 0.03). Daily use was linked to perceiving NPs as less harmful relative to combustible and smokeless tobacco, and more addictive relative to combustible, vaporized, and smokeless products (p < 0.05). Current and former use of combustible tobacco products, but not other substances, was common and varied by daily/non-daily use. Finally, adults who used daily were more likely to report a diagnosed mental or behavioral health condition (p = 0.002). Daily NP use reflects more intensive and contextually flexible use with distinct motivations and perceptions, underscoring heterogeneity in use patterns and the need for continued surveillance and longitudinal research on potential health implications.